PENGARUH MODEL PEMBELAJARAN KOOPERATIF JIGSAW DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA SEKOLAH DASAR - Warnis, Desmi; Junaidi, Junaidi; Syafruddin, Syafruddin (STKIP Pesisir Selatan, 2025)
This study aims to describe the effect of jigsaw cooperative learning model and learning motivation together on students' ability to write explanatory text. The research method used in this study is a quasi-experiment with a nonequivalent control group design (unequal pretest-posttest) pattern. The population in this study were all grade VI students in cluster 2 of Sungai Lasi kecematan consisting of 8 schools. In general, the jigsaw cooperative learning model (X1) has an effect of 13% on the ability to write explanatory text (Y) of elementary school students. However, the effect is still low as evidenced by the t-test result of -2.131. Learning motivation (X2) also has a significant effect of 56% on the ability to write explanatory text (Y) of elementary school students. The influence on motivation and ability to write explanatory text is evidenced by the results of the t test with a calculated t value of 2.561. The jigsaw cooperative learning model (X1) and learning motivation (X2) have an effect of 7.6% on the ability to write explanatory text (Y) of elementary school students. The effect of the jigsaw cooperative learning model and motivation together on the ability to write explanatory text is evidenced by the results of the f test of 3,585. The contribution of interest and motivation is 7.6%, the remaining 24% is influenced by factors outside the study. This is evidenced by the R2 value obtained in the multiple regression output of 0.076 or 7.6%.